PERBANDINGAN KONTAMINASI JAMUR Aspergillus sp PADA KACANG KEDELAI BERBIJI KUNING KUALITAS BAIK DAN JELEK YANG DIJUAL DI PASAR WIRADESA KAB. PEKALONGAN - Tuti Suparyati; Supriyo . (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Soybean is one of the leguminous plants which became the manufacture of many foods that contain lots of high protein and vegetable oil, which allows the fungus to grow.  Aspergillus sp is a fungus that can grow on soybeans, Aspergillus sp can cause infection include otomikosis, aspergillosis, and keratomikosis. Aspergillus sp can also secrete a toxin called aflatoxin, a known deadly and carcinogenic to humans and animals. Type  descriptive  research  with  cross  sectional  methode.  The  purpose  of  the  study  to compare the contamination of Aspergillus sp in yellow soybean seed of good or bad quality. The  results  showed,  Aspergillus  sp  contamination  in  yellow  soybean  seed  with  poor quality as much as 8 samples (53.335%), contamination of Aspergillus sp in yellow soybean seed with good quality as much as 4 samples (26.67%). Conclusion Aspergillus sp more contamination in yellow soybean seed with better quality than the crappy quality It is advisable for consumers to be careful in choosing good foods that will be consumed. KEYWORDS : Aspergillus sp. and Soybeans